Usage of Delaire facemask for treatment of Class III malocclusion - Terzieva-Petrovska Olivera; Petrovski Mihajlo; Petrovska Jasna (Medicinski fakultet i Klinika za stomatologiju, Niš, 2024)
Introduction: Different orthodontic appliances like reverse headgear and face masks are recommended for patients in the growing period with skeletal Class III malocclusion characterized by maxillary retrognathism, among moderate to severe cases. For most patients with Class III malocclusion seen in the early mixed dentition or late deciduous dentition, a Delaire face mask is the customary choice. Aim: Taking into account the aforementioned factors, as well as the growing importance of aesthetics in modern society, the main goal of this research was to analyse the relevant aspects of using face masks in the treatment of Class III malocclusion. Adequate literature research was performed to fulfil the main goal. Delaire face mask is commonly used for protraction of the maxilla. Conclusion: Some authors recommend early usage of face masks because they are more efficient in early treatment time and other studies do not show the relationship between the effect of maxillary face mask protraction and treatment timing. The principle of maxillary protraction is to apply tensile force on the circummaxillary sutures and stimulate bone apposition in the suture areas. Most of the authors conclude a positive effect of face mask treatment with significant improvement of skeletal parameters, and no significant difference between expansion/nonexpansion treatments. In conclusion, we can note that the effects of the treatment of Class III malocclusion with face masks largely depend on the knowledge of biological, orthopaedic and clinical aspects of their usage.